Determinations of the Inclusion Complex of Methylated β-Cyclodextrin with Styrene - Hu, Jie; Huang, Rong; Zhou, Zhiping (Asian Journal of Chemistry, 2010)
Inclusion complex of styrene with methylated β-cyclodextrin was prepared in aqueous media. NMR, TGA and UV-vis spectroscopy were used to characterize the complex. It was testified that the inclusion complex was formed between cyclodextrin and styrene and the stoichiometry tested was to be 1:1. It was found that the thermal stability of styrene encapsulated in cyclodextrin was much higher than that of free one. Then the association constants at different temperatures were determined using Benesi-Hildebrand linear regression. Thermodynamic parameters showed that the inclusion process was a spontaneous and exothermic one.